2012
DOI: 10.1155/2012/793708
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Agar Plate Screening and Solid-State Fermentation for the Prediction of Cellulase Production by Trichoderma Strains

Abstract: The viability of converting biomass into biofuels and chemicals still requires further development towards the reduction of the enzyme production costs. Thus, there is a growing demand for the development of efficient procedures for selection of cellulase-producing microorganisms. This work correlates qualitative screening using agar plate assays with quantitative measurements of cellulase production during cultivation under solid-state fermentation (SSF). The initial screening step consisted of observation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 28 publications
6
100
0
5
Order By: Relevance
“…For cellulase activity determination, at the next selection stages, various cellulose types were applied: Servacel (Goldbeck et al, 2012); Whatman No. 1 filter paper (Ruegger and Tauk-Tornisielo, 2004;Jahangeer et al, 2005;Florencio et al, 2012); and wheat bran (Ruegger and Tauk-Tornisielo, 2004;Damaso et al, 2012;Florencio et al, 2012). Application of cellulose with different physicochemical properties can affect the activity of cellulases.…”
Section: Application Of Cmc As a Substratementioning
confidence: 99%
See 3 more Smart Citations
“…For cellulase activity determination, at the next selection stages, various cellulose types were applied: Servacel (Goldbeck et al, 2012); Whatman No. 1 filter paper (Ruegger and Tauk-Tornisielo, 2004;Jahangeer et al, 2005;Florencio et al, 2012); and wheat bran (Ruegger and Tauk-Tornisielo, 2004;Damaso et al, 2012;Florencio et al, 2012). Application of cellulose with different physicochemical properties can affect the activity of cellulases.…”
Section: Application Of Cmc As a Substratementioning
confidence: 99%
“…At this stage, only few samples are subjected to a quantitative evaluation. Sazci et al (1986) and Florencio et al (2012) showed a correlation between the results obtained by semiquantitative and quantitative methods, but Goldbeck et al (2012) and Damaso et al (2012) pointed out that EI could not discern between isolates with different cellulase activities.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Biochemical tests viz., starch hydrolysis, gelatin liquefaction, casein hydrolysis, catalyst test, citrate test, cellulose hydrolysis, nitrate reduction test, hydrogen sulfide (H 2 S) production test and sugar fermentation test were performed 7,8 .…”
Section: Staining and Biochemical Characteristicsmentioning
confidence: 99%